Hydra: A decentralised group key management - Rafaeli, Sandro; Hutchison, David (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2002)
In this paper, we describe Hydra, a scaleable decentralised architecture to create and distribute symmetric cryptographic keys to large multicast-based groups. In order to support large multicast groups, the group is divided into a number of TTL-scoped regions. The purpose of having several regions is to achieve flexible and efficient key management, particularly in face of group membership changes. Hydra servers are designated as subgroup managers. They are responsible for managing group membership and distributing secret keys at the subgroup level. Hydra does not employ a manager for subgroup managers, and hence, it is not vulnerable to failure of single entities.